Identification of XPR-1, a progesterone receptor required for Xenopus oocyte activation - Tian, Jingdong (The National Academy of Sciences, 2000)
Quiescent full-grown Xenopus oocytes remain arrested at the G(2)/M border of meiosis I until exposed to progesterone, their natural mitogen. Progesterone triggers rapid, nontranscriptional responses that lead to the translational activation of stored mRNAs, resumption of the meiotic cell cycles, and maturation of the oocyte into a fertilizable egg. It has long been presumed that progesterone activates the oocyte through a novel nontranscriptional signaling receptor. Here, we provide evidence that a conventional transcriptional progesterone receptor cloned from Xenopus oocytes, XPR-1, is required for oocyte activation. Overexpression of XPR-1 through mRNA injection increases sensitivity to progesterone and accelerates progesterone-activated cell cycle reentry. Injection of XPR-1 antisense oligonucleotides blocks the ability of oocytes to respond to progesterone; these oocytes are rescued by subsequent injection of XPR-1 or the human progesterone receptor PR-B. Antisense-treated oocytes can be activated in response to inhibition of protein kinase A, one of the earliest known changes occurring downstream of progesterone stimulation. These results argue that the conventional progesterone receptor also functions as the signaling receptor that is responsible for the rapid nontranscriptional activation of frog oocytes.